Framework of Software Testing Based on Cloud Computing - Yang Bensehng; Yuan Xiangmeng; Huang Xiaoguang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
For the problem that efficiency is low and cost is high existing in the traditional software testing method, the paper tested software using cloud testing technology. It introduced related technologies including cloud testing, and described the design of overall architecture of the system in details, designed and implemented the scheduling module using a high priority first scheduling based on dynamic priority. The results of the Matlab simulation experiment show that this scheduling algorithm can reduce test cost and realize the automation of software testing under the condition of significantly improving test efficiency and resource utilization.